2022
DOI: 10.3389/fendo.2022.907874
|View full text |Cite
|
Sign up to set email alerts
|

An endometrial receptivity scoring system basing on the endometrial thickness, volume, echo, peristalsis, and blood flow evaluated by ultrasonography

Abstract: BackgroundEstablishing a successful pregnancy depends on the endometrium and the embryo. It is estimated that suboptimal endometrial receptivity account for one-third of implantation failures. Despite the indepth understanding of the processes associated with embryo-endometrial cross-talk, little progress has been achieved for diagnosis and treatments for suboptimal endometrial receptivity.MethodsThis retrospective study included women undergoing their first frozen-thawed embryo transfer (FET) cycles at our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…With regards to ovarian reserve follicular monitoring in the diagnosis of Polycystic Ovary Syndrome (PCOS), as well as prediction of oocyte quality and pregnancy outcomes, variables such as ovarian follicular diameter and volume, number of follicles, and ovarian stromal blood flow index were considered [ 48 ]. On the other hand, endometrial thickness and volume, endometrial morphology, and spiral arterial blood flow index are effective evaluation indicators [ 49 ]. There is a lot of ongoing research considering AI analysis of US images.…”
Section: Resultsmentioning
confidence: 99%
“…With regards to ovarian reserve follicular monitoring in the diagnosis of Polycystic Ovary Syndrome (PCOS), as well as prediction of oocyte quality and pregnancy outcomes, variables such as ovarian follicular diameter and volume, number of follicles, and ovarian stromal blood flow index were considered [ 48 ]. On the other hand, endometrial thickness and volume, endometrial morphology, and spiral arterial blood flow index are effective evaluation indicators [ 49 ]. There is a lot of ongoing research considering AI analysis of US images.…”
Section: Resultsmentioning
confidence: 99%
“…[ 21 ] Endometrial thickness, endometrial morphology, subendometrial blood flow, uterine spiral artery blood flow, and menstrual patterns are also determinants of fertility that affect uterine receptivity. [ 22 ] In a comprehensive prospective study conducted by Wang et al, [ 23 ] it was shown that the Covid 19 mRNA vaccine causes a short-term prolongation of menstrual cycle times. For this reason, Wang et al concluded that the immune response after vaccination might temporarily affect the hypothalamic-pituitary-ovarin and endometrial parts.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that endometrial patterns, such as triple-line configuration, patterns of a hyperechoic endometrium, and the presence of a central echogenic line detected by ultrasound as well as by the evaluation of endometrial blood flow, have more impact on the implantation potential as compared to endometrial thickness ( Gonen and Casper, 1990 ; Järvelä et al , 2005 ; Gingold et al , 2015 ; Navinchandra et al , 2016 ). Studies have also reported the combined approach of endometrial pattern together with thickness, and a scoring system for the prediction of pregnancy success during IVF ( Baruffi et al , 2002 ; Chen et al , 2010 ; Gingold et al , 2015 ; Khan et al , 2016 ; Navinchandra et al , 2016 ; Ugwu et al , 2022 ; Zhang et al , 2022 ). An IVF study reported that the triple-line endometrial pattern observed on the day of the administration of hCG was associated with an improved pregnancy rate compared to the homogenous, hyperechogenic, or intermediate endometrial pattern ( Gingold et al , 2015 ).…”
Section: Effect Of Endometrial Aging: Hormonal Cellular and Molecular...mentioning
confidence: 99%